Perioperative care of a patient suffering from colon cancer in consideration of International Classification for Nursing Practice (ICNP) - Pytel, Aleksandra; Kuberka, Izabela; Kołtuniu, Aleksandra; Rosińczuk, Joanna (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2017)
The paper presents a proposal of a nursing perioperative care plan devoted to the patients diagnosed with colon cancer, based on a case study. The schema of a medical interview prepared by the Nursing Board of Health and C-Hobic rate of care results were used in a detailed description of a case. The preparation of the care plan was based on ICNP® reference terminology, which nowadays plays an important part in the development of nursing.